Does Our English Teacher Education Need Re-Designing? - J. Bismoko (TEFLIN Journal: A publication on the teaching and learning of English, 2003)
Change has been regarded as inherent in any living organization for quite a long time, for its own development and to keep up its external relevance as part of the development. Individual or random responses to external sources for change, however, tend to cause internal inconsistency and inefficiency. On this occasion a number of current issues, potential to be sources for change, such as diversified outcomes, the school-based management, and the competence-based curriculum will be looked over in terms of its relevance to our English-teacher education. There are obviously other sources of change, and they will keep coming in, but when we feel they become too many, and they come too often, it is time to read between the lines, to grab their underlying spirit. Perhaps the time is here for us to get our English-teacher education re-orientated, and subsequently re-designed.